2002
DOI: 10.1016/s0169-5150(02)00078-6
|View full text |Cite
|
Sign up to set email alerts
|

Adding value to spatially managed inputs by understanding site-specific yield response

Abstract: Many mechanized crop producers and agribusinesses are fascinated with precision agriculture technology, but adoption has lagged behind the expectations. Among the reasons for slow adoption of precision agriculture technology is that initial users focused excessively on in-field benefits from variable-rate fertilizer application using regional average fertilizer recommendations. This article illustrates how greater use of site-specific crop response information can improve variable rate input application recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…The potential environmental benefits consist primarily of a reduction in the soil residual NO3-N concentration at the end of the growing season and consequently in reductions in leaching of NO3-N (Dinnes et al 2002). It should be noted that the EONR for a whole field is not necessarily equivalent to the mean of the EONR for subsections of fields (Bullock et al 2002). Thus, at times VRN affords the opportunity to reduce the total amount of NF applied while increasing crop yield.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential environmental benefits consist primarily of a reduction in the soil residual NO3-N concentration at the end of the growing season and consequently in reductions in leaching of NO3-N (Dinnes et al 2002). It should be noted that the EONR for a whole field is not necessarily equivalent to the mean of the EONR for subsections of fields (Bullock et al 2002). Thus, at times VRN affords the opportunity to reduce the total amount of NF applied while increasing crop yield.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to variable rate application of phosphorus or potassium fertilizers, the adoption of VRN has been extremely limited (Bullock et al 2002;Robert 2002). There are agronomic and economic reasons for this limited adoption of VRN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variable-rate seeding and pesticide application were used on 1%-3% of area depending on the crop. Bullock et al (2002) identified the lack of site-specific crop response information as a constraint to adoption of spatial crop management practices. Most variable rate input application is still based on whole field (WF) crop response information.…”
Section: Introductionmentioning
confidence: 99%
“…Most research into the mapping of agricultural returns has been focused at paddock and farm property scales within the field of precision agriculture. Numerous studies have undertaken paddock scale economic modelling to quantify the economic benefits of remedial measures such as more targeted soil treatments [13]. However, there have been few attempts to apply these models over large regions.…”
Section: Mapping Economic Returns Of Agricultural Land Usementioning
confidence: 99%